CLASSROOM INTERACTION STRATEGIES EMPLOYED BY ENGLISH TEACHERS AT LOWER SECONDARY SCHOOLS - Suryati, Nunung (TEFLIN Journal, 2015)
This article reports a study on teachers' use of interaction strategies in English Language Teaching (ELT) in lower secondary level of education. The study involved eighteen teachers from Lower Secondary Schools in Malang, East Java. Classroom observation was selected as a method in this study by utilizing Self Evaluation Teacher Talk (SETT) as the instrument. SETT, developed by Walsh (2006), was adopted as the observation protocol as it characterises teacher-student interaction. Thirty lessons taught by 18 teachers were observed. The findings revealed that much of the teacherstudent interaction in Lower Secondary Schools centred on the material mode, skill and system mode. The most frequent strategies were initiation response feedback (IRF) patterns, display questions, teacher echo, and extended teacher turns, while students' extended turns were rare. It is argued that in order to improve the Indonesian ELT, there is a need to provide an alternative to ELT classroom interaction. The article concludes by highlighting the importance of adopting some classroom interaction strategies that are more facilitative to students' oral communicative competence.